Competitive advantage gained from the use of helicopter emergency medical services (HEMS) for trauma patients: Evaluation of 1724 patients. Issue 5 (May 2019) - Weinlich, M.; Martus, P.; Blau, M.B.; Wyen, H.; Walcher, F.; Piatek, S.; Schüttrumpf, J.P.
Highlights: The highlight of this study is the use of outcome criteria for improved dispatch of HEMS criteria. Accidents with relevant head, abdominal and / or chest trauma (ISS > = 9). Signs of hemorrhagic shock, including low blood pressure. Glasgow Coma Scale < 8. When the overall time for the mission, ending in an appropriate trauma center, will be in favor of HEMS. Abstract: Objectives: The aim of the study was to analyze helicopter emergency medical service (HEMS) in comparison to EMS, in respect to patient's mortality and morbidity. Design: From a cohort of traumatized patients (n = 1724) prospectively enrolled in the German trauma registry (DGU-R) at Frankfurt University Hospital from 2009 to 2013, 1646 could be analyzed for in-hospital mortality and short-term outcome (GOS) at discharge and compared between HEMS and EMS. Measurements and main results: 129 patients (7.8%) died in the hospital. Unadjusted mortality was significantly lower in the HEMS group compared to EMS (p = 0.001). In a multiple logistic regression analysis after adjustment of variables including reanimation and age as the strongest predictors, in-hospital mortality was significantly reduced in HEMS (p = 0.014, OR = 0.21). Further predictors in the multiple logistic regression analysis were GCS > = 8 (p = 0.001), RRsys (p < 0.001), ISS at Head/Neck > = 3 (p = 0.003), and total ISS > = 9 (p < 0.001). Total rescue time and on scene time were associated with mortality (p < 0.001) but not included in the multiple logistic regression model. Without adjustment, short-term outcome (GOS) was significantly improved (p = 0.014). In a linear model, after adjusting for multiple variables including age, ISS Head/Neck > = 3, ISS Extremities > = 3, GCS > = 8, and RRsys as the strongest predictors (p < 0.001), the association remained significant (p = 0.043). Further predictors in the multiple linear regression analysis were total ISS > = 9 (p = 0.002), ISS abdomen (p = 0.001), and ISS Chest (p = 0.011). Conclusions: A significant improvement for in-hospital survival for HEMS could be demonstrated. Especially in Germany, with a high number of secondary call outs (about 44%) after EMS has already reached the traumatized patient, HEMS must be the first choice for severely injured trauma patients. Dispatch criteria for immediate alarm of HEMS are recommended under practical considerations.